Piezoelectric activation of peroxymonosulfate by MoS2 nanoflowers for the enhanced degradation of aqueous organic pollutants. Issue 3 (24th February 2021) - Liu, Shuhui; Jing, Binghua; Nie, Chunyang; Ao, Zhimin; Duan, Xiaoguang; Lai, Bo; Shao, Youyuan; Wang, Shaobin; An, Taicheng
Abstract : MoS2 NFs have exhibited abundant active sites in odd-number layers to piezoelectrically activate PMS for producing ˙OH and SO4 ˙ − in order to degrade organic pollutants. Abstract : Natural mechanical energies, such as wind, tidal waves, and water flow, widely exist in the environment and these inexhaustible natural mechanical energies can be utilized through piezoelectric materials for the degradation of aqueous organic pollutants in the environment. In this work, few-layered molybdenum disulfide nanoflowers (MoS2 NFs) were adopted as a piezocatalyst to activate peroxymonosulfate (PMS) with ultrasonic waves (US) as the mechanical force for phenol abatement. A much higher degradation efficiency was attained by the integrated US/MoS2 NFs/PMS system compared to other single systems, revealing the markedly synergistic effect of US and MoS2 on PMS activation. Moreover, density functional theory calculations were performed to fundamentally understand the charge distribution in a polarized MoS2 nanosheet under different strains and to understand the piezocatalytic properties of MoS2 nanosheets, as well as reaction pathways between PMS and carriers on the active edges of MoS2 for the production of free radicals. It was found that both sulfate radicals (SO4 ˙ − ) and hydroxyl radicals (˙OH) were produced in the US/MoS2 NFs/PMS system. However, SO4 ˙ − was quickly converted into ˙OH via a hydrolysis reaction under US, enabling ˙OH to be the primary reactive oxygen species for phenol oxidation. This work offers an efficient piezocatalyst to activate persulfate for water remediation. More importantly, it provides fundamental insights into the piezoelectricity in two-dimensional semiconducting materials and the mechanism in the piezocatalytic activation of persulfate. Results prove that the combination of piezoelectricity and advanced oxidation processes is promising for water pollution control, and provides a new idea for the application of inexhaustible natural mechanical energy in the environment for environmental remediation.